Effect of Instructions Emphasizing Velocity or Accuracy Given in a Random or Blocked Order on Performance Testing and Kinematics in Dart Throwing - van den Tillaar, Roland; Aune, Tore Kristian (Frontiers in Psychology, 2019)
The aims of this study were to investigate the effects of throwing instruction (i.e., velocity and accuracy) and testing order (random or blocked) on dart throwing performance testing and on the movement strategies leading to this performance. Twelve physical education students (9 men and 3 women, age: 24 ± 7.5; mass: 77.7 ± 15.8, height: 1.77 ± 0.06 m) performed dart throws with four different instructions, varying in priority regarding velocity and accuracy, instructed in a blocked and random manner. The main findings were that dart velocity decreased when the priority of accuracy increased. However, when accuracy was the main priority, accuracy increased only when measured for consistency. Testing order influenced peak joint kinematics of wrist flexion in addition to finger extension and the time of occurrence of elbow extension. Instructions emphasizing velocity and/or accuracy showed a clear speed-accuracy trade-off in dart throwing and thereby followed Fitts’ law. Testing order had a minor effect on the speed-accuracy trade-off. The blocked testing order appeared to increase performance outcomes that favored the priority set by the instruction in contrast to the random test order. These differences were based upon adjustments of joint movements, which were based upon the knowledge of the previous attempts. These adjustments were visible between the different instructions through changes in the execution timing of peak wrist flexion and elbow and finger extension.